New Strait Times , 24 April 2009 (The New Straits Times Press (M) Bhd, 2009)
Malaysia offers one of the best healthcare service in the region that has seen tremendous improvement in the las 3- years in terms of the number of hospitals, clinics, medical staff and quality of service.